Analisis Semantik Teks Agama Buddha: Makna, Simbolisme, dan Tafsiran Syair Citta Vagga - Nurhusna Dewi (Jurnal Budi Pekerti Agama Buddha, 2023)
This study examines the semantic aspects of the Citta Vagga (Mind Chapter) verses of the Dhammapada scriptures, focusing on the analysis of the meaning of keywords, symbolism, and philosophical interpretations in the text. The method used is a qualitative descriptive approach based on semantic analysis combined with hermeneutic methods to uncover the deep contextual meanings in Buddhist teachings. This study focuses on central concepts such as citta (mind), dukkha (suffering), and nibbana (liberation), as well as how the use of metaphor, personification, and repetition in the text helps convey the spiritual message and wisdom of the Buddha. The results of the study show that the layers of meaning in the Citta Vagga are very complex and rich in symbolic elements that refer to mind control as the core of Buddhist teachings. Furthermore, this research reveals the intricate relationship between linguistic structures and spiritual doctrines, demonstrating how ancient Pali texts employ sophisticated rhetorical devices to transmit timeless wisdom across generations.